Building an Applicative Model of Integration-Interconnection of Mathematics and Islamic Sciences - Musthofa, Muhammad Wakhid; Malahayati (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2024)
The idea of scientific integration-interconnection initiated by Amin Abdullah still cannot be applied in pure science study programs. The unique and very formal character of mathematics causes almost all lecturers of the Department of Mathematics and Mathematics Education to learn how to implement the concept of integration-interconnection when they teach some mathematical courses. This article offers a design for implementing the integration-interconnection paradigm of mathematics and Islam in the Tri Dharma of higher education activities for the Department of Mathematics and Mathematics Education. The integrative-interconnective model of mathematics and Islam includes an integrative learning, research, and community service model. We used the grounded theory method to form the integration-interconnection model. The resulting model is expected to be used as a guide for the academic community of the Department of Mathematics and Mathematics Education under the Islamic Religious Universities (Perguruan Tinggi Keagamaan Islam) in carrying out all activities of the Tri Dharma of higher education in terms of teaching and learning, research and community service.